Digital Image Quality in Medicine - Pianykh, Oleg S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Making a good diagnostic image is only the beginning; keeping it good and diagnostically sound is a much more difficult proposition, one that is often neglected or forgotten by clinical practitioners. With anything digital, the assumption of persistent original quality opens a Pandora$1 (Bs box of medical fiascos. Poorly selected image interpolation, thoughtlessly used compression, confused image enhancement options and the like can transform a good original into a useless clutter of pixels. This book is dedicated to learning better options. Intended for physicians, clinical practitioners and applications specialists, it provides a well-rounded introduction to meaningful diagnostic image housekeeping. The book presents the most important aspects of safe digital image workflows, starting from the basic practical implications and gradually uncovering the underlying concepts and algorithms. With an easy-to-follow, down-to-earth presentation style, the text helps you to optimize your diagnostic imaging projects and connect the dots of medical informatics.s
Introduction -- A Bit of History and Touch of Philosophy -- Image Interpolation -- Image Compression -- Image Enhancement -- Image Quality Online -- Image Display -- DICOM Calibration and GSDF -- Conclusion.
Keywords: Medicine; Medical records -- Data processing; Radiology, Medical; Medicine & Public Health; Medicine/Public Health, general; Imaging / Radiology; Health Informatics